Total anthocyanin and dietary fiber contents in blue corn cookies as affected by ingredients and oven types - Li, Jian (Kansas State University, 2009)
Anthocyanins, a group of pink to purple water-soluble flavonoids, are well known as naturally occurring pigments credited with numerous potential health benefits. However, they are sensitive to degradation by pH, light, and temperature. Blue corn (maize) is known to be high in anthocyanins (mainly cyanidin 3-glucoside). Citric and lactic acids and glucono-delta-lactone (GDL) are weak organic acids used by the food industry. Reel, convection, and impingement ovens are all used in the baking industry and they use different baking times and temperatures because they have different heat transfer coefficients. Cookies are popular snacks and might serve as a vehicle to deliver antioxidants and fiber. Preliminary tests showed that acids significantly increase the total anthocyanin content (TAC) remaining in the cookies when used at the 1.5% level (flour weight basis, fwb), then plateau up to the 6 % level. The interaction of three acids with three oven types (impingement oven 355F/4min, reel oven 400F/10min, and convection oven 360F/4min) were conducted to investigate their effects on the TAC remaining in blue corn based cookies. Cookie formula was based on AACC method 10-50D. Whole grain blue corn flour to wheat pastry flour ratio (80/20), guar gum level (1%, fwb), and water level (21.5%, fwb) were determined based on RSM analysis. All three acids affected TAC in cookie dough and final cookies by lowering their pH in the dough system. Citric acid retained the most TAC in the cookies. Cookie made with either GDL or citric acid provided larger spread, diameter, area, eccentricity, and crack ratio compared to the lactic acid. All three oven types significantly affected TAC in the cookies. The cookies baked by the convection oven contained the highest level of TAC. Oven types affected cookie spread but not diameter, area, eccentricity, brightness, or crack ratio. Cookies made with citric acid by convection retained maximum TAC (227±3.4 mg/kg). Cookies made with GDL by convection oven provided the greatest spread, crack, and eccentricity.
Keywords: Blue corn; Anthocyanin; Dietary fiber; Cookie; Oven; Acid; Agriculture, Food Science and Technology (0359)